2021
DOI: 10.4067/s0717-97072021000305251
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF GREEN SYNTHESIZED SILVER NANOPARTICLES ON CARNOSIC ACID CONTENT AND PHYSIO-BIOCHEMICAL PROPERTIES OF Rosmarinus Officinalis L

Abstract: In biosynthesis of metal nanoparticles, it is possible to replace the old chemical synthesis methods with new environment-friendly procedures. In this study, AgNP was synthesized using extracts of Rosmarinus officinalis L. leaves, and then its effect on biochemical characters, antioxidant enzymes activity, and finally carnosic acid content was studied with its various concentrations. UV-visible spectroscopy was utilized to identify the formation of synthesized AgNP. Synthesized AgNP was confirmed the absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Mohammadi et al (2016) observed a decline in Chl content at a concentration of 10 ppm TiO 2 NPs in dragonhead ( Dracocephalum Moldavia L.) plants [ 24 ]. Such discrepancies may be attributed to various factors including genetic and environmental variations among species, the specific plant parts studied, growth conditions, treatment duration, sampling methods, and nanoparticle synthesis processes [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mohammadi et al (2016) observed a decline in Chl content at a concentration of 10 ppm TiO 2 NPs in dragonhead ( Dracocephalum Moldavia L.) plants [ 24 ]. Such discrepancies may be attributed to various factors including genetic and environmental variations among species, the specific plant parts studied, growth conditions, treatment duration, sampling methods, and nanoparticle synthesis processes [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%